2017
DOI: 10.1016/j.polymdegradstab.2016.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of enhancement of intumescent fire retardancy by metal acetates in polypropylene

Abstract: The effects of cobalt acetate (CoAc), manganese acetate (MnAc), nickel acetate (NiAc) and zinc acetate (ZnAc) as fire retardant additive in intumescent polypropylene (PP) formulations containing PP/ammonium polyphosphate (APP)/pentaerythritol (PER) are reported. The limiting oxygen index (LOI) and vertical burning (UL94) tests and cone calorimetry were used to quantify the enhancement. Environmental chamber rheometry, thermal gravimetric analysis and the morphology of the residual char were used to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 29 publications
0
38
0
Order By: Relevance
“…Char formation has been enhanced in polyethylene, using functionalised graphene oxide [87]; in PMMA using graphene oxide and a nickel-aluminium layered double hydroxide [88]; in ABS copolymer, with graphene nanosheets combined with a metal hydroxide [89]; in polyamide 6 using graphene supported cobalt oxide and nickel oxide [90]; and in epoxy resins using silica, attached to cobalt-aluminium layered double hydroxide spheres [91]. Enhancement of the barriers can be achieved in intumescent systems, where gas is released within the molten polymer, causing significant swelling, and so increasing the effectiveness of the thermal barrier [92], for example in polyethylene [93], polypropylene [94] and polystyrene [95]. Carbon nanotubes (CNT) have also been used as potential fire retardant additives, given their similarity to carbonaceous char, with mixed success [96].…”
Section: Fire Retardantsmentioning
confidence: 99%
“…Char formation has been enhanced in polyethylene, using functionalised graphene oxide [87]; in PMMA using graphene oxide and a nickel-aluminium layered double hydroxide [88]; in ABS copolymer, with graphene nanosheets combined with a metal hydroxide [89]; in polyamide 6 using graphene supported cobalt oxide and nickel oxide [90]; and in epoxy resins using silica, attached to cobalt-aluminium layered double hydroxide spheres [91]. Enhancement of the barriers can be achieved in intumescent systems, where gas is released within the molten polymer, causing significant swelling, and so increasing the effectiveness of the thermal barrier [92], for example in polyethylene [93], polypropylene [94] and polystyrene [95]. Carbon nanotubes (CNT) have also been used as potential fire retardant additives, given their similarity to carbonaceous char, with mixed success [96].…”
Section: Fire Retardantsmentioning
confidence: 99%
“…Cone calorimeter test has a good correlation with real fire disaster and provides a wealth of information about the combustion behavior, so it is often used to estimate flame properties of materials. Among indexes provided by CCT, heat release rate (HRR) and the total heat release (THR) are very important to evaluate the developing, spreading, and intensity of fires . Figure shows HRR curves of flame retardant WSP composites.…”
Section: Resultsmentioning
confidence: 99%
“…Among indexes provided by CCT, heat release rate (HRR) and the total heat release (THR) are very important to evaluate the developing, spreading, and intensity of fires. [23][24][25] Figure 2 shows HRR curves of flame retardant WSP composites. From Figure 2, it can be observed that the HRR curve of pure PP presents a sharp peak during a short time range of 0 to 225 seconds and its peak HRR (pHRR) is as high as 1290.5 kW/m 2 .…”
Section: Cone Calorimeter Testmentioning
confidence: 99%
“…Intumescent formulations normally consist of three basic ingredients, namely, an acid source as a catalyst, a carbon source, and a gas source or blowing agent . In the case of the acid source, compounds of acids, ammonium salts, and phosphates are often used.…”
Section: Introductionmentioning
confidence: 99%